Vulvovaginal candidiasis and vaginal microflora interaction: Microflora changes and probiotic therapy - Sun, Zhongwen; Ge, Xinnuo; Qiu, Bo; Xiang, Ze; Jiang, Chun; Wu, Jian; Li, Yuan (Frontiers in Cellular and Infection Microbiology, 2023)
Vaginal microbiome is mutually beneficial to the host and has a significant impact on health and disease. Candida species, including Candida albicans, are part of the mucosal flora of most healthy women. Under suitable conditions, they can live in the vulvovaginal mucosa, resulting in symptomatic vulvovaginal candidiasis (VVC). Based on the analysis of 16S ribosomal RNA gene sequences, great progress has been made in exploring the composition and structure of vaginal bacterial community. Moreover, researchers have conducted several studies on whether vaginal microbiome will change during VVC infection. In addition, it has been reported that vaginal colonization of probiotics in vaginal microorganisms, especially Lactobacillus, can effectively reduce the risk of VVC and treat VVC. This review aims to summarize the changes of vaginal microflora during VVC infection, and further point out the possibility of using lactic acid bacteria as probiotics to treat VVC, so as to reduce the adverse consequences of VVC infection and reduce the expensive treatment cost.